Change Management in Developing Educational Organization at SMA Darul Ulum 2 Featured BPPT Jombang and MA International Standard Amanatul Umah Pacet Mojokerto - Winarto, Winarto; Qomar, Mujamil; Patoni, Achmad; Maftukhin, Maftukhin; Akhyak, Akhyak (Technium Social Sciences Journal, 2021)
Management is a collaboration that involves all components in an educational organization so that it runs effectively and efficiently. Change management occupies an important position in rearranging educational organizations into different shapes, sizes, characteristics, and places so that educational organizations experience changes for the better in the future. This study aims to analyze and find change management in developing educational organizations at SMA Darul Ulum 2 Unggulan BPPT Jombang and MA Bertaraf Internasional, Amanatul Umah Pacet. This study used a qualitative approach with a phenomenological type and a multisite design. The results showed: the change design of educational organizations is; planned change, the force change, orientation and mission vision, preparing, unfreezing, change, and refreezing. Management of change with; motivation to realize high quality schools, coordination and communication, team work, socialization of the change agenda, mentoring, individual level changes, group level changes, organizational level changes through the POAC stage, namely: planing (integrated planning), organizing (organizing), actuating (implementing power full) and controlling. Followed by the leader's desire to continuously make changes (continuous improvement) based on billah to realize an output that has an advantage, reword. While the implications of changes in educational organizations include: internal implications and external implications. The formal findings of this study are Integrated Change Management Teams in developing educational organizations that are animated from the three research focuses.